OPTIMIZATION PROCUREMENT CONTRACT SERVICE LEGAL VIOLATION - Helma Widya (Jurnal Scientia, 2023)
Crimes committed jointly are included in the form of participation (delneming) is an understanding that includes all forms of participation/involvement of a person or persons both psychologically and physically by carrying out each act so as to give rise to a criminal act, namely a criminal act corruption in the procurement of goods/services for the Padang Lawas district government. The problems in this research are regarding the factors that cause corruption to occur jointly, regarding the qualifications of criminal acts of each perpetrator of a criminal act of corruption carried out jointly and the criminal responsibility of perpetrators of a criminal act of corruption in the procurement of goods/services carried out jointly in the Decision. This type of research is normative juridical research, using a statutory approach and a case approach. This research uses literature study which aims to collect secondary data. The data analysis used is qualitative data analysis. Based on the results of research and discussion, factors that cause corruption can be encouragement from within oneself, namely desire, intention to commit an evil act and encouragement from outside the human being, such as the environment (organization), opportunities to commit deviations and so on. Proving the criminal corruption case carried out by the chairman of the DPRD of Padang Lawas Regency jointly, it was proven that the defendant deliberately abused the authority that belonged to him, by issuing a principle permit. Examination at the trial of the defendant's actions fulfilled the criminal elements in the Public Prosecutor's subsidiary indictment. The defendant's action in issuing a principle permit for the construction of the Padang Lawas Regency Government Center area was a form of "act of abusing authority which has benefited other people or corporations (in this case PT. Bungo Pantai Brothers).